PECULIARITIES OF PHARMACISTS’ PROFESSIONAL TRAINING AT THE UK UNIVERSITIES (Comparative Professional Pedagogy, 2022)
The article reveals the peculiarities of pharmacists’ professional training in Great Britain. It is established that pharmaceutical education in Great Britain is aimed at obtaining professional knowledge, abilities and skills for successful implementation in all potential directions of a pharmacist's career (social pharmacy, medical pharmacy, industrial pharmacy, and pharmaceutical research). It is clarified that pharmaceutical education in Great Britain has been fundamentally changed since 2012 due to the introduction of «integrated» educational programs for the training of pharmacists. The structure of pharmaceutical education is described in detail. It is defined that the recognized qualification for professional registration with the Royal Pharmaceutical Society of Great Britain is the 4-year MPharm program, upon completion of which a one-year internship program is mandatory. The requirements and main stages for obtaining the professional qualification of a pharmacist in Great Britain are described. Peculiarities of MPharm educational programs at the universities of Great Britain, namely structure, content, duration of study, compliance with European educational standards are analyzed. The educational program of the Master of Pharmacy (MPharm) at the University of Bradford, which is based on the 4-year “bachelor” model, its structure, and stages of study are presented. There are four options for students to master the MPharm program for completing it: obtaining a certificate of higher education, a diploma of higher education, a bachelor's degree in pharmaceutical research and a master's degree in pharmacy. The requirements for the awarding of degrees and program learning outcomes are characterized. It is stated that substantial attention in the training of pharmacists is paid to the study of clinical pharmacy, which in the near future will give them the right to write prescriptions. It is concluded that the goal of training pharmacists is to preserve and improve the health of the population due to providing highly qualified pharmaceutical care.
Keywords: professional training; pharmacist; Great Britain; pharmaceutical education; educational programs; training